Exploring the Role of Cinematic Techniques in Shaping Audience Emotions - Chawla, Arkin (Journal of Neonatal Surgery, 2025)
Cinema is widely recognized as the most emotionally absorbing art form, able to evoke profound emotive reactions through the orchestration of visual and audio elements. This study investigates how cinematic techniques, specifically cinematography, lighting, color, framing, camera movement, and lens design, shape audience feeling, with an emphasis on Indian cinema's aesthetic traditions and practices. In the Indian cinematic milieu, emotion serves as both narrative essence and visual strategy. The paper analyzes works by filmmakers and cinematographers such as Satyajit Ray and Subrata Mitra, Mani Ratnam and P.C. Sreeram, and Sanjay Leela Bhansali and Binod Pradhan to show how different approaches, from poetic realism to visual spectacle, create distinct emotional grammars. Indian film develops a distinct blend of realism, stylization, and impact by combining indigenous rasa principles with modern cinematographic approaches. Finally, the study contends that cinematic processes actively generate emotion by transforming light, color, and movement into visceral manifestations of feeling. In this way, the cinematographer becomes an emotional co-author, converting cultural and psychological experiences into visual form and transforming cinema into an art of seeing and feeling the human soul.